PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PELECEHAN SEKSUAL DITINJAU MENURUT SOSIOLOGI HUKUM ISLAM - Ashikin, Nurul (STAIN Bengkalis, 2023)
Moral crimes and sexual violence are recognized in the norms of all world religions, so religious values ​​are universal. This must be avoided at the executive level, because the role of community values ​​also greatly influences the police. Legal and non-legal factors must be prioritized in the formulation and implementation of sex offender laws. For example, people's perception that women are a source of sexual harassment, feeling guilty for sexual violence. The question shows that it is very difficult, as well as the formulation of errors that lead to many interpretations. The research used is analytical and descriptive, using normative legal research and using secondary data. Secondary information is obtained through literature research or documentary research. All data and information is then processed through qualitative data analysis. In the next bill, sexual harassment should be ruled as a crime against good morals. Forms of sexual harassment must be determined according to developments in crime in society, but still based on the results of research by qualified legal experts.